2015
DOI: 10.1109/jsen.2014.2360885
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Design of a Dual-Range Force Sensor for Achieving High Sensitivity, Broad Bandwidth, and Large Measurement Range

Abstract: Force control is very crucial in nanoimprint lithography (NIL). It is necessary to develop a high-performance force sensor to provide real-time force feedback for the control process. Due to the unique procedure of NIL, the developed force sensor should include a high sensitivity, broad bandwidth, and large measurable range. However, these characteristics are normally conflicting in nature and cannot be physically avoided by any force transducers so far. To address this problem, this paper presents a novel dua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, these approaches to advance the RFS increase the system's complexity and leave open challenges regarding the sensitivity and the cross-coupling between the axes, which must be solved by the mechanical design of the force sensor. When enhancing the force sensor's sensitivity through optimizing its mechanical design, reduced measurement bandwidth and lower load rating must be considered [26]. Conversely, it is observed that the sensitivity of the ECS does not negatively impact the measurement bandwidth.…”
Section: Analysis Of Performance Variancementioning
confidence: 99%
“…However, these approaches to advance the RFS increase the system's complexity and leave open challenges regarding the sensitivity and the cross-coupling between the axes, which must be solved by the mechanical design of the force sensor. When enhancing the force sensor's sensitivity through optimizing its mechanical design, reduced measurement bandwidth and lower load rating must be considered [26]. Conversely, it is observed that the sensitivity of the ECS does not negatively impact the measurement bandwidth.…”
Section: Analysis Of Performance Variancementioning
confidence: 99%
“…Bekhti designed a multi-axis force/torque sensor by adopting changes in the geometry of the compliant mechanism as a performance index and indicated that the response of the sensor will be nonlinear under applied external forces [12]. Several displacement and force sensors with multiresolution and large-measurement-range features were also presented by [13] and [14]. (ii) Compound sensors.…”
Section: Measurement Science and Technologymentioning
confidence: 99%
“…The proposed technique has been solved by using heuristic algorithm to obtained a trade off between maximizing fairness, maximizing spectrum utilization, reflecting the priority among sensor data and avoiding unnecessary spectrum handoff. A heuristic algorithm has been used in [ 193 ] to solve the problem of optimum design of a dual range force sensor for obtaining high sensitivity, broad bandwidth and large measurement range. In [ 194 ], the authors have used an heuristic algorithm to solve a multi-objective optimization approach for sensor arrangement in a complex indoor environment.…”
Section: Solution Types/algorithmsmentioning
confidence: 99%